Teachers implementing Zimbabwean sign language regulatory frameworks for deaf learners in special schools - Reward Kwashira (International Journal of Studies in Inclusive Education, 2024)
Effective implementation of sign language-based instruction is crucial for providing quality education to Deaf learners at special schools. Teachers experienced challenges to effectively implement sign language policies for the Deaf learners in Zimbabwean special schools. However, this study explores how teachers implement sign language regulatory frameworks for Deaf Learners in special schools. Drawing on qualitative data from teachers, headmasters, school inspectors, and psychologists. The findings revealed critical gaps in the in-service training and professional development opportunities available to teachers serving Deaf students. Despite teachers reporting difficulties with sign language fluency and inadequate understanding of Deaf culture and pedagogy, the study found a disconnect between teachers' expressed needs and the perspectives of district-level officials, who often did not perceive additional training as necessary. This study further highlights the heavy reliance on support from external donor organizations and NGOs to provide teachers with limited sign language workshops and resources. This overreliance on precarious external funding sources compromises the sustainability and scalability of professional development initiatives. The study's implications call for a comprehensive, government-led strategy to ensure all teachers in Deaf schools receive robust, long-term training in sign language, Deaf education methodologies, and Deaf cultural competence. Strengthening the capacity of the teaching workforce is essential for upholding the rights of Deaf learners to receive instruction in their primary language and achieving meaningful implementation of sign language policies. This study contributes vital empirical evidence to inform policy reforms and teacher training programmes to support using Zimbabwean Sign Language as a medium of instruction for the Deaf.